PRAYER AND VIGILANCE: A BIBLICAL AND PHILOKALIAN APPROACH TO THE RENEWAL AND PROTECTION OF THE NOUS - Hendi Hendi; Magdalena Hananing Triyanti; Tjenny Liesar; Kezia Ariesa S Sara S (Manna Rafflesia, 2024)
This article examines the biblical and Philokalian approach to renewing and protecting the nous or intellect (Romans 12:2; 1 Corinthians 2:17), proposing that prayer and nepsis (vigilance) are essential strategies for mitigating the influence of logismoi and passions. Analysis reveals that these practices are vital in cultivating authentic Christian spirituality. The Philokalia invites a reevaluation of spiritual perspectives, offering a novel framework that integrates an investigative tool, therapeutic technique, and theoretical insights into the human mind. This study highlights how these ancient practices can be adapted to modern psychotherapeutic interventions, providing a transformative approach to revitalizing our nous faculties. The findings underscore the relevance of the Philokalia in contemporary spiritual and psychological contexts, introducing innovative methods for addressing spiritual and emotional challenges in today's world. This article aims to bridge ancient spiritual wisdom with contemporary therapeutic practices, offering new insights and practical applications for enhancing mental and spiritual well-being.